Potential therapeutic role of pharmacological sympathectomy in Martorell ulcer - Baglivo, Mirko; Baronio, Manuela; Dieumo Ngongan, Nina Arnelle; Romagnoli, Stefano; De Gaudio, Raffaele; Bertelli, Matteo (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Martorell ulcer (MU) is a rare complication of arterial hypertension. It was first described in 1945 by the Spanish cardiologist Fernando Martorell, who reported 4 clinical cases [1]. A few cases of MU have been treated with pharmacological sympathectomy [2]. Here we report another small group of cases of MU treated in this manner. Sixteen patients with MU, aged 69 to 92 years, were selected. A precise diagnosis of MU was made by checking the Martorell diagnostic inclusion criteria: anterolateral site in the lower third of the leg, diastolic hypertension in the lower third of the leg, hyperpulsation of the arteries of the leg, absence of arterial calcification and other causes of the ulcer, possible presence of symmetrical lesions and stronger pain in the horizontal position [1].